Hypoglycaemic, hypolipidaemic and antioxidant effects of blackberry beverage consumption in streptozotocin-induced diabetic rats. (October 2016) - Azofeifa, Gabriela; Quesada, Silvia; Navarro, Laura; Hidalgo, Olman; Portet, Karine; Pérez, Ana M.; Vaillant, Fabrice; Poucheret, Patrick; Michel, Alain
Abstract: Abnormal glucose metabolism, hyperlipidaemia profiles and high levels of radical oxygen species (ROS) are classic features of diabetes. This study evaluates the effect of the consumption of two different blackberry beverages at 25 and 12.5% given orally for 40 days to rats with streptozotocin induced diabetes. The lower dose of blackberry (12.5%) non-statistically decreased glycaemia (−10.4%), triacylglycerols (−4.6%) and cholesterol (−21.0%). These differences were not statistically significant. The higher dose of blackberry (25%) significantly decreased glucose (−48.6%), triacylglycerols (−43.5%) and cholesterol (−28.6%). The higher dose of blackberry (25%) improved plasma antioxidant capacity, reduced the levels of lipid peroxidation in plasma (−19%) and in kidney (−23%). Blackberry intake did not improve catalase, suggesting that attenuation of oxidative stress via scavenging activities rather than improving the activities of antioxidant enzymes. These results provide promising data for this blackberry as a dietary adjuvant to the pharmacological management of diabetes.